Enhancing Students’ Performance in Integrated Project Course through Collaborative Learning and Open Artificial Intelligence Chatbot - Binti Affendi, Norhazaliana; Binti Ghazali, Nurbaya; Binti Abu Bakar, Rohani (Jumper: Journal of Educational Multidisciplinary Research, 2024)
Numerous students faced challenges related to specific concepts, deeming it essential to seek supplementary guidance for the successful completion of their mandatory final semester projects within the Integrated Project Course. This need arose early in the project development phase, and these individuals consistently encountered difficulties in bringing their projects to fruition. The challenges stemmed from the intricate nature of the course material and the inadequacy of suitable guidance. As a result, some students occasionally delivered incomplete and below-par project outcomes. Consequently, this research endeavors to enhance students' final semester project performance by employing collaborative learning methods and integrating an Open Artificial Intelligence Chatbot as interventions. The study was conducted during the session II  2022/2023 in the Department of Information and Communication Technology at Polytechnic Sultan Abdul Halim Mu’adzam Shah, involving 12 students enrolled in the Integrated Project Course and receive score mark below five during their Demonstration One presentation session. Data collection included rubric scores and reflective journals, which were analyzed based on rubric percentages before and after the intervention. The findings of the study indicated an improvement in rubric scores before and after the intervention, signifying an enhancement in students' project-related performance. Additionally, the reflective journal provided insights into the students' learning experiences with both interventions. This research contributes to educators' comprehension of effective methods for elevating students' performance in Integrated Project Course by leveraging contemporary technologies and approaches. Future research initiatives could further diversify teaching and learning methods in Integrated Project through the organization of workshops specifically addressing current technology and knowledge pertinent to the development of final semester projects.